Implementasi Peta Digital untuk Mendukung Pelayanan Informasi Kepemilikan Lahan di Desa Grujugan Kabupaten Kebumen - sausan sausan; Popy Laras Puspita; Gavrilla Claudia; Luqman Nawawi; Argadhana Nugrohosiwi (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
Grujugan Village has a short and medium term plan (RPJMD) to create a spatial information system and digital map. The information system will be used for village spatial planning. However, the problem found is that the existing map of the Grujugan Village area does not meet the requirements of a digital map. The existing map is still a sketch map that does not contain coordinate data. This community service aims to help overcome this problem by making a digital map of Grujugan Village. The method of implementing this community service consists of observation and preparation stages, implementation stages, and activity evaluation stages. At the implementation stage there is a digital map making stage. The method of making digital maps uses Quantum GIS and data collection using drones and the My Track application. The result of this community service activity is a digital map of Grujugan Village. The benefit of this community service is that Grujugan Village currently has a digital map that can be used to facilitate information services in Grujugan Village.